2011
DOI: 10.1371/journal.pone.0028643
|View full text |Cite
|
Sign up to set email alerts
|

Lunar Phase-Dependent Expression of Cryptochrome and a Photoperiodic Mechanism for Lunar Phase-Recognition in a Reef Fish, Goldlined Spinefoot

Abstract: Lunar cycle-associated physiology has been found in a wide variety of organisms. Recent study has revealed that mRNA levels of Cryptochrome (Cry), one of the circadian clock genes, were significantly higher on a full moon night than on a new moon night in coral, implying the involvement of a photoreception system in the lunar-synchronized spawning. To better establish the generalities surrounding such a mechanism and explore the underlying molecular mechanism, we focused on the relationship between lunar phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 42 publications
6
34
0
Order By: Relevance
“…) and in the reef fish S. guttatus (Fukushiro et al . ) did in fact find differences in core circadian gene expression between full and new moon, consistent with the observations reported here and the model presented in Fig. .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…) and in the reef fish S. guttatus (Fukushiro et al . ) did in fact find differences in core circadian gene expression between full and new moon, consistent with the observations reported here and the model presented in Fig. .…”
Section: Discussionsupporting
confidence: 92%
“…Some vertebrates, for example the reef fish S. guttatus (Fukushiro et al . ), also link reproduction to the lunar cycle, as do a wide variety of other marine phyla, and it will be interesting to determine whether cell division rates also show a lunar association in these other species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interconnections between circadian and lunar rhythms are found in some marine organisms, such as corals and fishes (Levy et al, 2007;Vize, 2009;Fukushiro et al, 2011;Ikegami et al, 2014). It is suggested that the rhythmic expression of melatonin may serve as a possible transducer between lunar spawning rhythmicity and circadian rhythms in fishes (Ikegami et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the circadian rhythm, lunar cycles in marine organisms are most prominently involved in reproductive events, such as synchronous mass spawning (Tessmar-Raible et al, 2011). Lunar-controlled reproductive rhythms are widespread and are of fundamental importance for many marine organisms, including corals, sea urchins, mollusks, and fishes (Vize, 2009;Fukushiro et al, 2011;Ikegami et al, 2014). For these marine species, the lunar cycles provide a steady timeframe that can be used for developmental synchronization and mass spawning, even across widespread populations (Tessmar-Raible et al, 2011).…”
Section: Introductionmentioning
confidence: 99%